Correlation Between Chess Game and Improving Critical Thinking Skills of Binjai City High School Students - Josep Perlindungan Halawa; Vincentius Gokmaruli Sidabutar; Dirly Laurensius Perangin Angin (Ikatan Sarjana Olahraga Republik Indonesia (Kabupaten Kampar), 2025)
Objectives: This study investigated the correlation between chess playing and critical thinking ability enhancement among high school students in Binjai City, North Sumatra, Indonesia. Methods: A correlational study was conducted with 40 high school students (ages 15-18) from Binjai City. Participants completed the Watson-Glaser Critical Thinking Appraisal (WGCTA) before and after an 8-week chess intervention program. Chess skill was assessed using standardized rating systems and playing experience. Results: Results demonstrated a significant positive correlation between chess skill rating and critical thinking abilities (r = 0.663, p < 0.001). Post-intervention critical thinking scores showed significant improvement (t = -9.251, p < 0.001) with a large effect size (Cohen's d = 1.35). All five WGCTA subscales showed positive correlations with chess proficiency. Conclusion: Chess playing significantly correlates with enhanced critical thinking abilities in Indonesian high school students. The intervention demonstrated measurable improvements in inference, assumption recognition, deductive reasoning, interpretation, and argument evaluation skills.